1996
DOI: 10.1074/jbc.271.50.31783
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Amyloid Protein Precursor Is Localized in Nerve Terminal Preparations to Rab5-containing Vesicular Organelles Distinct from Those Implicated in the Synaptic Vesicle Pathway

Abstract: In order to localize amyloid protein precursor (APP) in nerve terminals, we have immunoisolated vesicular organelles from nerve terminal preparations using antibodies to Rab5 and synaptophysin. These immunoisolates were then analyzed by electron microscopy and by immunoblotting. The synaptophysin immunoisolates represented a nearly homogeneous population of small synaptic vesicles, with less than 10% contamination by other organelles, and very little APP. In contrast, Rab5 immunoisolates contained, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 35 publications
6
62
0
Order By: Relevance
“…2F), similarly to syd vesicles and to what has been previously described (32,33). Together, these results suggest that syd is associated with at least two classes of vesicles.…”
Section: Syd Is Associated With Vesicles Of Distinct Size Andsupporting
confidence: 72%
“…2F), similarly to syd vesicles and to what has been previously described (32,33). Together, these results suggest that syd is associated with at least two classes of vesicles.…”
Section: Syd Is Associated With Vesicles Of Distinct Size Andsupporting
confidence: 72%
“…Alzheimer APP is localized in nerve terminal preparation to Rab5-containing endocytic trafficking organelles distinct from those implicated in the synaptic vesicle pathway (60). An axonal cell-surface protein, APP, is internalized with recycling synaptic membrane proteins but is subsequently sorted away from synaptic vesicles (61). In addition, the present study revealed that Rab5A plays a critical role during the endocytosis of exogenous ␣-synuclein followed by the induction of acute cytotoxic effect.…”
Section: Figmentioning
confidence: 69%
“…For example, blocking of APP endocytosis by deletion of its NPxY motif (Perez et al, 1999) or by overexpression of dominant-negative dynamin mutants impairs Ab production (Chyung and Selkoe, 2003;Carey et al, 2005). Most studies suggest that amyloidogenic processing proceeds in early or late endosomes (Golde et al, 1992;Haass et al, 1992;Koo and Squazzo, 1994;Ikin et al, 1996;Rajendran et al, 2008;Sannerud et al, 2011). The predominant localization of bsecretase to endosomal compartments (Huse et al, 2000;Pastorino et al, 2002;Sannerud et al, 2011) and the requirement of an acidic milieu (as in the case of endocytic vesicles) for its activity support this model (Vassar et al, 1999).…”
Section: Cellular Trafficking Of App Controls Processing Fatesmentioning
confidence: 96%